A Study On The Teaching Method of Speaking English by Using Debat as Used By Debat Coach at ILF of the University of Muhammadiyah Malang - pria Fambudi, Angga Okta; Hendro Wicaksono, Bayu (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
A Study On The Teaching Method of Speaking English by Using Debat as Used By Debat Coach at ILF of the University of Muhammadiyah Malang